Frequency Chirped Intensity Modulated Mid-Infrared Light Source Based on Optical Parametric Oscillation - Kun Li; Suhui Yang; Xin Wang; Zhuo Li; Jinying Zhang (IEEE Photonics Journal)
Optical carried microwave radar (OCMR) has better resistance to turbulence and scattering than conventional laser radar for using intensity modulated laser beam as detection medium. Intensity modulated mid-infrared source is the key to mid-infrared OCMR system. A frequency chirped intensity modulated mid-infrared light source with tunable wavelength is presented. Single frequency output from a non-planar ring oscillator (NPRO) was modulated via a Mach-Zehnder electro-optic modulator (EOM). The modulation frequency was tuned from 10 MHz-2.1 GHz. The modulated light was amplified via a two-stage ytterbium-doped fiber amplifier (YDFA). The amplified 1064 nm laser was used to pump a signal light resonance optical parametric oscillator (OPO). The nonlinear crystal was a 50 mm long magnesium oxide doped periodically-poled lithium niobite (MgO:PPLN) crystal. Single frequency oscillation was realized by adding a 0.2 mm-thick Fabry-Perot (F-P) etalon in the resonator. When the pump power was 15.2 W, the idler output power at mid-infrared was 2.16 W. The maximum pump-idler conversion efficiency was 16.5%. The wavelength of the idler light was tuned from 3.1 μm to 3.8 μm by changing the temperature of the MgO:PPLN crystal. The frequency chirping linearity with respect to time was 0.9937 on average with modulation frequency tuned from 10–350 MHz. The frequency instability was less than 1.5 Hz in 200 seconds at a modulation frequency of 300 MHz.